Acetone Prospect as an Additive to Allow the Use of Castor and Sunflower Oils as Drop-In Biofuels in Diesel/Acetone/Vegetable Oil Triple Blends for Application in Diesel Engines - Aguado-Deblas, Laura (Molecules, 2020)
The present paper investigates the feasibility of using acetone (ACE) in triple blends with fossil diesel (D) and straight vegetable oils (SVOs) as alternative fuel for diesel engines. In this respect, ACE is selected as an oxygenated additivedue to its favorable propertiesto be mixed with vegetable oils and fossil diesel. In fact, the very low kinematic viscosity allows reduces the high viscosity of SVOs. ACE’s oxygen content, low autoignition temperature, and very low cloud point and pour point values highlight its possibilities as an additive in D/ACE/SVO triple blends. Moreover, ACE can be produced through a renewable biotechnological process, an acetone–butanol–ethanol (ABE) fermentation from cellulosic biomass. The SVOs tested were castor oil (CO), which is not suitable for human consumption, and sunflower oil (SO), used as a standard reference for waste cooking oil. The viscosity measurement of the ACE/SVO double blend was considered crucial to choose the optimum proportion, which better fulfilled the specifications established by European standard EN 590. Moreover, some of the most significant physicochemical properties of D/ACE/SVO triple blends, such as kinematic viscosity, cloud point, pour point, and calorific value, were determined to assess their suitability as fuels. The blends were evaluated in a conventional diesel generator through the study of the following parameters: engine power, smoke emissions, and fuel consumption. Despite the low calorific value of ACE limits its ratio in the mixtures due to engine knocking problems, the experimental results reveal an excellent performance for the blends containing up to 16-18% of ACE and 22-24% of SVO. These blends produce similar engine power as to fossil diesel, but with slightly higher fuel consumption. Considerable reductions in emissions of air pollutants, as well as excellent cold flow properties are also obtained with these triple blends. In summary, the use of these biofuels could achieve a substitution of fossil diesel up to 40%, independently on the SVO employed.